If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = 6x Reorder the terms: 5 + 3x = 6x Solving 5 + 3x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 5 + 3x + -6x = 6x + -6x Combine like terms: 3x + -6x = -3x 5 + -3x = 6x + -6x Combine like terms: 6x + -6x = 0 5 + -3x = 0 Add '-5' to each side of the equation. 5 + -5 + -3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 0 + -5 -3x = 0 + -5 Combine like terms: 0 + -5 = -5 -3x = -5 Divide each side by '-3'. x = 1.666666667 Simplifying x = 1.666666667
| 15=4x-1+4 | | c/8=6.5 | | y=7/10(-4)+7 | | 8y+9=73+y | | 13n+11=5n+219 | | 24-(14x-8)-(3+12x)=4-(8x+11) | | 5a+2=17a-5 | | 3v=0.6 | | 3/4z=1/4z+12 | | n^3/2=729 | | -4y=20+4 | | (4k+3)(3k-5)= | | x/2-x/3=5 | | n+x+27=7 | | 1=5k-6k | | x^2-8xb+15b+1=0 | | 8=-5-6m-5 | | 4x+7+3x+5=2x+2 | | 5n+6=3(2n+10) | | 8-10x=93-45x | | 4w+19=149 | | 6(-3.2941)-4y=-24 | | 6*x+6*x+3=48 | | -5z+23=126 | | 6x+10x=78+x | | 3k^2+k-10=0 | | c=0.7y+50 | | -7y-16=16 | | 6x-4(2/7x+2)=-24 | | 3x-(7x-5)=1 | | 3(3+3r)+1=37 | | (3/8)^2/(3/7+3/14) |